Two rotator cuff tear repair techniques for sovraspinatus tendon tear: transosseous sharc-ft vs single row repair - Pellegrini, Andrea (Acta Biomed, 2020)
BACKGROUND: Despite rotator cuff repair techniques have developed significantly in last decade, pushed by the progress in technology and materials, the treatment of rotator cuff tears and re-tears is still a big challenge for shoulder surgeons. The aim of this study is to perform clinical and radiological evaluation (ultrasound and MRI) of patients treated with transosseous sharc-ft, and single row techniques for sovraspinatus rotator cuff tear at 6, 12 and 24 months follow up. METHODS: Twenty-eight consecutive patients who underwent arthroscopic repair for rotator cuff tear were enrolled in the study and divided in two different groups: group A (14 patients) underwent a single row technique repair; group B (14 patients) underwent a transosseous sharc-ft technique repair. All participants had MRI or ultrasound examination confirmed full-thickness tears of sovraspinatus tendon before surgery. All the patients underwent clinical evaluation at 45 days, 3 months, 6 months, 12 and 24 months post-operatively with VAS, Dash, Constant and ASES score. Diagnostic ultrasound examination was performed at 6 months follow up while the MRI examination at 1 and 2 year follow up. RESULTS: The whole primary variables didn’t show any significant difference and the groups were homogenous (age, Goutallier fatty infiltration, VAS, DASH, Constant, ASES). Some statistically significant differences are visible at discrete variables in a specific time: Dash at 12 months and Constant at 24 months show a significant improvement versus single-row technique. CONCLUSION: The arthroscopic transosseous repair technique with sharc-ft showed excellent results with little significant statically difference between this technique and the single row for this kind of lesion after 1 year of follow-up. Clinical data from this study confirmed, with the help of ultrasound examination and MRI, the excellent clinical outcome obtained by the patients. Further studies are needed to find differences between these techniques in the repair of large and massive rotator cuff lesions. (www.actabiomedica.it)